[tex]a)\\\\-2:(7-11)=-2:(-4)=\frac{2}{4}=\frac{1}{2}\\\\b)\\\\\frac{ 6-(-7)*(-2) }{-4}= \frac{ 6-14 }{-4}=\frac{-8}{-4}=2\\\\c)\\\\ (-2-4)*(-6):(-3)^2 =(-6)*(-6):9=36:9=4[/tex]
[tex]d)\\\\ \frac{ (-3)*(-2-10)}{7-9}= \frac{ (-3)*(-12)}{-2}=\frac{ 36}{-2}=-18\\\\e)\\\\(-2)^3+45:(-3)^2=-8+45:9=-8+5=-3\\\\f)\\\\ \frac{15-(-2)*4 }{-11+4}+ \frac{5-2}{ 2-3 }= \frac{15-(-8) }{-7}+ \frac{3}{ -1}=\frac{15+8}{-7}-3=\\\\=-\frac{23}{7}-3=-3\frac{2 }{7}-3 =-6\frac{2}{7}[/tex]
[tex]g)\\\\ (-2)* \frac{1-4}{4} =-2*\frac{-3}{4}=\frac{6}{4}=1\frac{2}{4}=1\frac{1}{2}\\\\h)\\\\\frac{12-20}{2}*3=\frac{-8}{2}*3=-4*3=-12\\\\i)\\\\\frac{-8+4}{3}*\frac{6}{-1+3}=\frac{-\not{4}^2}{\not{3}^1}*\frac{\not{6}^2}{\not{2}^1}=-4[/tex]